Використання прибутку підприємства в умовах здійснення модернізації й оновлення виробництва - Следь, О.М. (Стратегія і механізми регулювання промислового розвитку, 2013)
Досліджено підходи до формування та використання чистого прибутку підприємств. Встановлено систему пропорцій поділу прибутку на частини, що капіталізуються (кошти навиробничий розвиток, формування резервного фонду), і частини, що споживаються (кошти на виплату дивідендів, матерільне стимулювання персоналу та соціальний розвиток підприємства). Запропоновано метод визначення структури використання чистого прибутку підприємства, що забезпечує приріст коштів, які спрямовуються на розвиток виробництва. Исследованы подходы к формированию и использованию чистой прибыли предприятий. Установлена система пропорций разделения прибыли на части, которые капитализируются (средства на производственное развитие, формирование резервного фонда), и части, которые потребляются (средства на выплату дивидендов, материальное стимулирование персонала и социальное развитие предприятия). Предложен метод определения структуры использования чистой прибыли предприятия, обеспечивающий прирост средств, направляемых на развитие производства. The article studies the characteristics of using the profits of enterprises under production modernization. It was found that one of the main reasons for insufficient technical and technological renewal of production base is limited own funds of enterprises, and the lack of the state innovation stimulation tool. The experience in the modernization and renovation of production at leading machine-building enterprises and economic justification of purposeful patterns of the net profits distribution indicate the need and possibility of establishing a rational structure of the net profit, part of which is directed at the development of production. Research approaches to the formation and use of the enterprise profits revealed a system of proportions of profit division, that covers the capitalized part (funds for industrial development, the formation of the reserve fund), and part of that is consumed (funds for dividend payments, financial incentives for staff and social development of the company). A method of determining the structure of using the net profit that provides the growth of funds allocated for the development of production is proposed. The need for the modernization of production makes it necessary to increase the portion of the net profit that is capitalized, that is, the proportion of funds allocated for the development of production. An important prerequisite for this is to provide a simultaneous increase in profits across other directions, or at least not decrease the admission of the profit that is consumed. In particular, this applies to the funds allocated for the social development, reproduction and accumulation of the intellectual capital as a major factor in the technological development and for the improvement of production. It is also necessary to strengthen the financial incentives for the workers who muster new techniques and technologies to improve the efficiency of production and to prevent resistance from the personnel. The net profit used for investment in the modernization purposes is advisable to distribute in view of the natural changes in the structure of fixed assets due to an accelerated rate of growth in the value of machinery and equipment compared to the cost of building and construction works through the use of appropriate correction factor for the proportion of active part of fixed assets.